Feeding intensity and daily mussel consumption of Rapa whelk (Rapana venosa) in the north-western Black Sea - Stadnichenko Svitlana; Kurakin Aleksandr (Oceanological and Hydrobiological Studies)
Based on an experiment carried out in the north-western Black Sea (Snake Island), the feeding behavior of the Rapa whelk (Rapana venosa Valenciennes, 1846) was analyzed in relation to its size (N = 58; shell height: 30–90 mm). Mediterranean mussels (Mytilus galloprovincialis Lamarck, 1819) were placed in experimental cages with R. venosa to be used as food. It was found that the size of the prey was determined by the size of the predator. The mussels with a shell length of 20–40 mm were most affected by R. venosa. It was determined that the predator's contribution to the deposition of mussel shells in the bottom sediments is also associated with its size. Feeding intensity varies from 41 mg to 99 mg of the total mass of mussels per 1 g of the total mass of R. venosa per day, depending on the size of the predator. The daily consumption of mussel soft tissue varied from 0.189 g ind.−1 per day−1 in small R. venosa specimens to 0.917 g ind.−1 per day−1 in large predators. Regression equations were obtained between the length and mass of the mussels consumed (total mass, soft tissue mass and shell mass) and the shell height of the predator.